Conjugate heat transfer analysis in two square enclosures with bounded and partitioned conductive wall - Marhama Jelita; Sutoyo; Saleh, Habibis (Penerbit Universiti Kebangsaan Malaysia, 2018)
Conjugate heat transfer in two square enclosures are studied numerically in the present article. Effects of a finite side wall thickness and a finite partition thickness on the fluid flow pattern, and heat transfer rate are studied comprehensively. An iterative finite difference procedure is employed to solve the governing equations. The study is performed for different wall thickness and thermal conductivity ratio. The extreme size of the wall thickness for both enclosure is obtained under specific conditions. The maximum ratio of the heat transfer rate is achieved by adjusting the solid size to proportional to the thermal conductivity ratio.